2011
DOI: 10.1002/mds.23688
|View full text |Cite
|
Sign up to set email alerts
|

Blind randomized controlled study of the efficacy of cognitive training in Parkinson's disease

Abstract: The aim of this study was to analyze the efficacy of a cognitive training program on cognitive performance and quality of life in nondemented Parkinson's disease patients. Participants who met UK Brain Bank diagnosis criteria for Parkinson's disease, with I-III Hoehn & Yahr, aged 50-80, and nondemented (Mini-Mental State Examination ≥ 23) were recruited. Patient's cognitive performance and functional and quality-of-life measures were assessed with standardized neuropsychological tests and scales at baseline an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
118
5
11

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(145 citation statements)
references
References 46 publications
11
118
5
11
Order By: Relevance
“…In the case of the patients with more prominent executive deficits, there has been interest in agents that may have an alerting capacity such as modafanil, [40] as well as drugs targeting the noradrenergic system such as atomoxetine [33]. Another therapeutic strategy which is gaining an evidence base for early cognitive deficits in PD is cognitive training, [41,42] although it remains to be seen whether demonstrated improvements on neuropsychological tests translate into real-world improvements in cognitive function.…”
Section: How Can We Treat the Cognitive Deficits Of Pd?mentioning
confidence: 99%
“…In the case of the patients with more prominent executive deficits, there has been interest in agents that may have an alerting capacity such as modafanil, [40] as well as drugs targeting the noradrenergic system such as atomoxetine [33]. Another therapeutic strategy which is gaining an evidence base for early cognitive deficits in PD is cognitive training, [41,42] although it remains to be seen whether demonstrated improvements on neuropsychological tests translate into real-world improvements in cognitive function.…”
Section: How Can We Treat the Cognitive Deficits Of Pd?mentioning
confidence: 99%
“…Certainly, there is already evidence in favor of computerized cognitive training in healthy subjects by demonstrating improvements in working memory and changes in brain biochemistry concerning the density of cortical dopamine D1 receptors [McNab et al 2009]. Some research on cognitive rehabilitation in patients with PD revealed promising results in terms of supporting mental activity [Cerasa et al 2014;Petrelli et al 2014;Zimmermann et al 2014;Reuter et al 2012;París et al 2011;Sammer et al 2006]. Thus, drug therapy combined with computerized cognitive training might achieve a more favorable benefit when compared with pharmacotherapy alone [Brusa et al 2013].…”
Section: Introductionmentioning
confidence: 99%
“…They can affect how people are able to interact with technological devices and training materials. However, despite these deficits, computerized cognitive training has been shown to be feasible and effective in various pathological conditions such as Parkinson's disease [87] and stroke [88]. Computerized interventions and tests might actually offer optimized and adjustable interfaces to overcome some of these deficits, e.g.…”
Section: Technology Aspectsmentioning
confidence: 99%